2023
DOI: 10.21182/jmisst.2023.00913
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) is a popular surgical technique for treating lumbar spinal disorders. While it offers advantages over traditional open surgery, it is not without complications. The prevention, early detection, and proper management of complications are crucial in achieving successful outcomes with MI-TLIF. Patient selection, surgical technique, and postoperative monitoring play key roles. Advances in imaging, tools, and implant design contribute to reducing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Despite the use of expandable cages in MIS TLIF, studies have shown that while disc height can be effectively increased, there is still limited improvement observed in postoperative sagittal alignment including segmental and lumbar lordosis. Moreover, it has been observed that patients who had preoperative lordotic segment often experience a kyphotic change after undergoing MIS TLIF ( 11 - 13 ). Therefore, different designs of expandable cages were developed to address this problem ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of expandable cages in MIS TLIF, studies have shown that while disc height can be effectively increased, there is still limited improvement observed in postoperative sagittal alignment including segmental and lumbar lordosis. Moreover, it has been observed that patients who had preoperative lordotic segment often experience a kyphotic change after undergoing MIS TLIF ( 11 - 13 ). Therefore, different designs of expandable cages were developed to address this problem ( 14 ).…”
Section: Introductionmentioning
confidence: 99%